Therapeutic study of rosacea by Azithromycin and Metronidazole - Al-harchan, Naseer A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Rosacea is a chronic disease that requires long-term systemic and or local therapy, which carries risk for systemic complications and adverse reactions and high recurrence rate. Patient and methods: Two groups of rosacea patient with at least 8 inflammatory papules and pustules, moderate to severe facial erythema (22 patient treated with oral azithromycin versus 18 patient treated with oral metronidazole) were studied at single medical center (medical city of Baghdad: department of dermatology and venereology , both for 60 days, Subjects were evaluated monthly for up to three months to determine the relapse rate. Main outcome measures: Inflammatory papules and pustules were counted at each visit, relapse were determined by the appearance of a clinically significant increase in number of papules and pustules. Erythema were classified to three grades: - 0=Nil, 1=mild to moderate, 2=severe. Patient satisfaction also classified to three grades: 0=no satisfaction, 1=partial satisfaction, 2=full satisfaction. Results: Most of the patients respond to treatment measured by at least 70% reduction in the number of inflammatory lesions. (21 patient versus 14 patient) completed the study and compare by assessing:- erythema improvement and papule and pustule count reduction and percentage of occurrence of side effects and relapse, and subjective assessment of the degree of patients satisfaction with their treatment Erythema were reduced after two months of treatment:- (56.6% to 33.3% for azithromycin group versus 43.5% to 66.7% for metronidazole group).Mean papules count reduced from (36.9 to 10 for azithromycin group versus 25.8 to 11 for metronidazole group). Mean pustule count reduced from (2.95 to 0.33 for azithromycin group versus 2.92 to 0.5 for metronidazole group). The percentage of relapse was 16.7% versus 83.3% for azithromycin and metronidazole group respectively. Complete satisfactions were 70% versus 30% and side effect were 20% versus 80% for azithromycin and metronidazole group respectively. Conclusion: For the above results treatment of rosacea by azithromycin is more effective, safer thanmetronidazole, although the coast is little higher.